Effects of Physical Working Condition on Effective Teaching and Learning in Public Secondary Schools of Bwari Area Council Abuja, Nigeria - Marcus Garvey Orji; Akhimien Emmanuel; Nweke Pearl Iheoma; Muhammad Ridwan (BIRCU, 2021)
The status of physical working conditions/facilities especially in Nigerian public secondary schools today appears to be of great concern to educators. It seems that the provisions of these school facilities have dwindled over the years, perhaps due to increase in school enrolment rate which had led to population explosion in public schools. The objective of this study was to examine the effect of physical working condition on effective teaching and learning in public secondary schools of Bwari Area Council Abuja, Nigeria. The study is a survey research and the population of the study consists of 540 teachers of 11 public secondary schools in the Council with sample size of 230 determined using Taro Yamane’s formula. Primary data was used through the administration of questionnaire, and the formulated hypotheses tested by Kendal coefficient of concordance method. The findings of the study revealed that Conducive physical working condition; Instructional materials, learning facilities like computers, flips chart and audio-visual disc increases students learning and enhance academic performance; Functional facilities like classrooms furniture’s and libraries improve students’ reading habits, hence increase their performance. Also, the location of Schools encourages parents to enroll their children in Public Secondary Schools. The study concluded that Physical working conditions and school location are effective tool for educational development in general, has a positive impact on the students ‘academic performance. It recommended among others that Federal Capital Education Board Abuja and other Government agencies urgently need to upgrade teaching facilities to meet up with modern demands of secondary school education. Digital facilities should be provided in schools. While the schools’ managers on their part should also try to maintain and manage them very well, also Public Secondary Schools should be located in an area that can provide adequate Playgrounds, gardens and common rooms to enable the students have good recreational activities. And all stakeholders in the school system like Parents, Teachers Association (PTA) have a duty to rise up and contribute to upgrade School facilities in Bwari Area Council of Abuja.